Diagnosis and management of conductive hearing loss in children with trisomy 21. (22nd May 2018) - Stewart, Robbie; Gallagher, Donna; Leyden, Peter
Abstract : Aim: The objective of this study is to review the prevalence and degree of hearing loss in children with trisomy 21, their response to intervention and the presence of concomitant pathologies. The project will also highlight the experiences of the children from their parents' and guardians' perspective and the link between perceived service quality and an objective improvement in their hearing after rehabilitation. Methods: All patients with trisomy 21 who were referred to district general otolaryngology outpatient clinics between 2014 and 2016 were included. A retrospective analysis of the medical notes and audiograms along with a qualitative questionnaire to the children's parents was utilised to gather the information. Results: The study showed that 77% (17/22) of children suffered from hearing loss, with a moderate degree being most prevalent. The majority of patients (14/17, 82%) were managed conservatively, undergoing a period of watchful waiting (9/17, 53%) or receiving hearing aids (5/17, 30%) and 3 of 17 (17%) were managed with grommet insertion. The improvement in hearing with hearing aids was comparable with grommet insertion and hearing aids scored highest in the post‐intervention qualitative assessment with grommet insertion scoring the lowest. Conclusions: Functional hearing has been shown to be key in developing speech and language skills. In children with trisomy 21, behavioural and anatomical abnormalities make the diagnosis and intervention technically more challenging. This study demonstrates that in the absence of other otological symptoms, hearing loss can be managed effectively and with the least distress to the children with hearing aids.